1981
DOI: 10.1056/nejm198101223040403
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Galactosylhydroxylysyl Glucosyltransferase, an Enzyme of Collagen Synthesis, in a Family with Dominant Epidermolysis Bullosa Simplex

Abstract: Members of a family with dominant epidermolysis bullosa simplex were found to have a deficiency of galactosylhydroxylysyl glucosyltransferase (GGT), an enzyme catalyzing the glucosylation of galactosylhydroxylysyl residues in the biosynthesis of collagen. The enzyme's activity was low in serum, skin tissue, and cultured skin fibroblasts, although no abnormality was found in three other intracellular enzymes of collagen biosynthesis. Mixtures of serum samples from patients and healthy controls gave the expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…The decrease in GGT activity in a Finnish family with dominant EBS, accompanied by a markedly decreased urinary excretion of glucosylgalactosylhydroxylysine, was reported earlier (28). Among the families tested, this was the only family with a deficiency of GGT activity, indicating that this feature is unique to this family and does not represent a typical finding in EBS patients (28). In addition, Savolainen and co-workers (28) reported that the decrease in GGT activity correlated with the severity of the disease.…”
supporting
confidence: 73%
See 3 more Smart Citations
“…The decrease in GGT activity in a Finnish family with dominant EBS, accompanied by a markedly decreased urinary excretion of glucosylgalactosylhydroxylysine, was reported earlier (28). Among the families tested, this was the only family with a deficiency of GGT activity, indicating that this feature is unique to this family and does not represent a typical finding in EBS patients (28). In addition, Savolainen and co-workers (28) reported that the decrease in GGT activity correlated with the severity of the disease.…”
supporting
confidence: 73%
“…We have examined heterozygous LH3 knock-out mice and mouse embryonic fibroblasts (MEF ϩ/Ϫ ) at the ultrastructural level as well as cells from a human model of LH3 deficiency, an epidermolysis bullosa simplex (EBS) family member known to exhibit a decrease in GGT activity. The decrease in GGT activity in a Finnish family with dominant EBS, accompanied by a markedly decreased urinary excretion of glucosylgalactosylhydroxylysine, was reported earlier (28). Among the families tested, this was the only family with a deficiency of GGT activity, indicating that this feature is unique to this family and does not represent a typical finding in EBS patients (28).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The biological significance of the GGT activity of LH3 in the biosynthesis of collagen types IV and VI has been demonstrated from the studies of LH3-deficient mice (28 -30). In addition, defective GGT activity resulting from four polymorphic nucleotides in the non-coding region of Plod3 was detected in a family with dominant epidermolysis bullosa simplex (31,32). In another recent finding, two heterozygous mutations in the Plod3 coding region have been associated with a rare syndrome of congenital malformations affecting several connective tissues and organs (33).…”
mentioning
confidence: 98%